Topical issues of physical therapy for gunshot lesions of the diaphysis of the shoulder - Sergiy Kalmykov; Yuliya Kalmykova (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to consider the features of physical therapy for gunshot lesions of the diaphysis of the shoulder. Material & Methods: theoretical analysis and generalization of modern scientific and methodological literature data on the features of the use of rehabilitation equipment for gunshot shoulder injuries. Results: the peculiarities of the application of physical therapy devices after gunshot lesions of the shoulder diaphysis are determined, the features of the application of kinesitherapy, therapeutic massage and physiotherapeutic treatment at different periods of the pathological process. Conclusion: physical therapy is an integral part of the medical rehabilitation of the wounded with gunshot injuries of the shoulder and depends on the amount of damage to the muscular apparatus, the immobilization method, the severity of the general condition of the wounded and the period of the pathological process and rehabilitation measures.